Math, asked by tejasmishra390, 2 months ago

Find the value pls write real answer and only those know answer ​

Attachments:

Answers

Answered by Gauthmathspark
1

Answer:

x = 1

Step-by-step explanation:

{ (\frac{ - 3}{5} })^{2x + 1}  =  \frac{ - 27}{125}  \\ { (\frac{ - 3}{5} })^{2x + 1} = { (\frac{ - 3}{5} )}^{3}  \\ 2x + 1 = 3 \\ 2x = 3 - 1 \\ 2x = 2 \\ x = 1

Answered by Gauthmath

Answered by ashishsinghjsr2004
1

Answer:

(-3/5)^2x+1 = -27/125

(-3/5)^2x+1 = (-3/5)^3

therefore, 2x+1 = 3

2x = 3-1

2x = 2

x = 2/2

x= 1

Similar questions